Chest drainage or repeated thoracentesis for pleural infections: a clinical dilemma - Carmine Salerni; Michele Mondoni; Giovanni Sotgiu (Pneumonia)
Abstract Pleural infection is a key clinical challenge, especially in immunocompromised patients and in those with pulmonary comorbidities. Its incidence has increased owing to antibiotic resistance and aging of the population. While international guidelines recommend chest tube (CTD) placement for complicated parapneumonic effusions (CPPE), the optimal strategy for fluid drainage is debated. Repeated therapeutic thoracentesis (RTT) could be an alternative to help patient mobility and reduce infectious risk. Studies on RTT demonstrated efficacy similar to that of CTD, mainly when combined with intrapleural fibrinolytic therapy and DNase, whereas others showed higher treatment escalation rates. In the issue of the Journal, Charron et al. show that RTT, combined with IPFT and DNase, decreases both pleural drainage duration and hospital stay when compared with chest drainage, without increasing mortality, surgical referral, or complication rates. However, methodological concerns, including variability in pleural infection definition, retrospective design, and centre-dependent treatment strategies, might limit the generalizability. Large-scale randomized controlled trials are needed to definitively establish its role.